Glucose Required for Tissue Formation and Its Effects on Cane Yield, Recoverable Sugar, and Sugar Yield - Nunik Eka Diana; Supriyadi; Djumali; Budi Santoso; Anik Herwati; Sri Yulaikah; Supriyono; Ruly Hamida; Aprilia Ridhawati; Abdurrakhman (International Journal of Agronomy)
Glucose in sugarcane affected cane yield, recoverable sugar, and sugar yield. Glucose is available since the formation of the stems and stored until sugarcane is ready to be harvested. Information regarding the need for glucose to form sugarcane plant tissue is still not widely available. So, research was conducted to determine the quantity of glucose to form sugarcane plant tissue and its relation to cane yield, recoverable sugar, and sugar yield obtained. The research was carried out at the Karangploso Research Station and Laboratory of Plant Chemistry, Indonesian Sweeteners and Fiber Crops Research Institute, in July 2016–September 2017. A split plot design with two factors and three replications was utilized. The main factor was the growth phases, namely, the vegetative phase and maturity phase, while the other factor was sugarcane varieties, namely, PS-881 (early mature), JR-01 (early-middle mature), Kenthung (early-middle mature), and Bululawang (middle-late mature). The measurements of nitrogen, carbon, and the ash content of the leaves and stems were at 5 months (representing the growth period) and 9 months (representing the ripening period). The results showed that quantities of 1.962–2.160 kg and 2.066–2.113 kg glucose were required to form each kg of leaf and stem tissue depending on the growth phase and variety. Glucose requirements in the maturing phase affected the cane yield, recoverable sugar, and sugar yield as much as by 51.48%, 57.60%, and 58.26%, respectively.